For fertile advice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
This booklet introduces the role of fertilisation in plants in relation to soil characteristics, with fertiliser recommendations for 16 selected crops, including rice, cassava, onions and tomatoes, and gives practical suggestions on fertiliser use...